Trade, Innovation and Optimal Patent Protection - David Hémous; Simon Lepot; Thomas Sampson; Julian Schärer (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper provides a first comprehensive quantitative analysis of optimal patent policy in the global economy. We introduce a new framework, which combines trade and growth theory into a tractable tool for quantitative research. Our application delivers three main results. First, the potential gains from international cooperation over patent policies are large. Second, only a small share of these gains has been realized so far. And third, the WTO's TRIPS agreement has been counterproductive, slightly reducing welfare in the Global South and for the world. Overall, there is substantial scope for policy reform.
Keywords: F13; D43; O34; 330; trade policy; innovation; growth; patents; TRIPS